The Practice of Religious Environmentalism: a Bourdieuian Study of Qur'anic and Hadith-Based Ecological Ethics at Pondok Pesantren Al-Hidayah Karangsuci Purwokerto - Izza, Farah Nuril; Tarto; Intan, Putri; Hibaurrohman, Imam Labib (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
This study examines the practice of religious environmentalism in an Indonesian Islamic boarding school by applying Pierre Bourdieu’s theory of practice. Focusing on Pondok Pesantren Al-Hidayah Karangsuci Purwokerto, this article analyses how Qur’anic and hadith-based ecological ethics are practiced in everyday lives of santris. This study employed ethnographic approach. The data were collected through participant observation, in depth interviews, and document analysis. The findings of the study demonstrate that, first, environmental practices are the result of institutional rules and routines, santris’ religious capital, as well as their habitus. Second, religious knowledge plays as symbolic capital that legitimizes ecological behaviour. However, its translation into embodied practice is strongly supported by prior habitus and structural conditions. Third, santris of this study express compliance, negotiation, and resistance in their practice of religious environmentalism. Fourth, this study argues that the practice of religious environmentalism in pesantren should be understood as the dynamic process shaped by power, disposition, and institutional authority rather than as the direct outcome of normative religious teachings.